Recent advances in nano-materials for packaging of electronic devices - Zhang, Shuye; Xu, Xiangyu; Lin, Tiesong; He, Peng (Journal of materials science. Materials in electronics, 2019)
In recent years, Moore’s law had a remarkable effect on predicting the development of semiconductor technology. As the size of devices shrinks to micro scale or nano scale, Intel’s newest 10-nm logic technology is scheduled to start product shipments before the end of 2017. Moore’s law will not die out, as the research scale reaches the atomic scale, “new devices” and new interconnection methods are urgently needed. In this paper, based on emerging interconnection requirement, the contribution to the advanced electronic packaging containing novel nano-materials, such as the carbon nanotubes, nanoparticles sintering, interconnection of nano-solder, nano-silver and surface plasma nano-welding are discussed. For the next 5–10 years, two new types of interconnect solutions are gaining attentions: solder joint alternatives and Cu electrode alternatives. The former uses new materials such as graphene, carbon nanotubes and nanowires to replace traditional solder joints. The latter uses optical media to replace the traditional Cu metal. In general, advanced materials will make more and more outstanding contributions in the development of electronic packaging in the next 10–20 years.